Why should models talk to each other? A multipronged modelling strategy as an operational framework to guide adaptive watershed management in the Bay of Quinte Basin, Ontario, Canada - Carlos Alberto Arnillas; Aisha Javed; Alex Neumann; Lamees Shah; George B. Arhonditsis (Ecological Modelling, 2026)

Modelling sediment diagenesis processes in a freshwater ecosystem experiencing transient external phosphorus and iron loading - Tao Xu; Alex Neumann; Yasasi Fernando; Maria Dittrich; David Depew; George Arhonditsis (Ecological Modelling, 2026)

Species dispersal and community assembly facing the Atlantic meridional Overturning circulation - Everton Giachini Tosetto; Christophe Lett; Sigrid Neumann-Leitão; Ariane Koch-Larrouy; Nicolas Barrier; Alex Costa da Silva; Ramilla Assunção; Camila Artana; Alina Nathanael Dossa; Guillaume Morvan; Arnaud Bertrand (Progress in Oceanography, 2026)

Coupling sedimentary cycling with eutrophication severity under transient external phosphorus and iron loading regimes - Tao Xu; Alex Neumann; Maria Dittrich; Yasasi Fernando; John Gibson; Ramin Farnood; David Depew; George B. Arhonditsis (Ecological Modelling, 2026)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Characterization of biogeochemical cycles in agricultural watersheds: Integrating regional modelling assessment with downstream water quality - Aisha Javed; Ali Saber; Alex Neumann; Carlos Alberto Arnillas; George B. Arhonditsis (Journal of Environmental Management, 2025)

Agitation dredging of silt and fine sand with Water Injection Dredging, Tiamat and Underwater Plough: a case study in the Port of Rotterdam - Sterre Neumann; Alex Kirichek; Andre van Hassent (Journal of Soils and Sediments, 2024)
Purpose Agitation dredging has gained popularity as an environmentally friendly and cost-effective method for port maintenance. One of the advantages of agitation dredging is the ability to transport sediments out of the port area using natural currents. The effect of the different agitation methods on sediment and water properties has rarely been investigated in a single pilot project. This research aims to study the effects of agitation methods in silt and sand-dominated areas that are frequently maintained. Methods The effects of water injection dredging, (WID) underwater ploughing (UWP) and Tiamat on sediment properties are investigated in the Port of Rotterdam. In-situ measurements and laboratory measurements are carried out to determine changes in the bed level, the particle size distribution of the bed, the turbidity in the water column and the dispersion distance of the sediment plume due to agitation dredging. Results The results of the in-situ monitoring of the agitation pilots allow a comparison of the changes in sediment and water properties before, during and after agitation dredging. The production, advantages and limitations of the tested agitation dredging methods are discussed. Conclusion The in-situ measurements show that WID, Tiamat and UWP can be successfully used for the agitation of sediments and their removal from the silt and sand-dominated areas. The production of the tested agitation methods is higher for silty than sandy sediments. In general, the selection of the agitation equipment can be made based on environmental regulations, sediment properties and hydrodynamic conditions.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Diel vertical migration and seamount stepping stones promote species connectivity from coastal to offshore insular systems in the Tropical Southwestern Atlantic - Everton Giachini Tosetto; Christophe Lett; Sigrid Neumann‐Leitão; Ariane Koch‐Larrouy; Nicolas Barrier; Alex Costa da Silva; Julie Salvetat; Arnaud Bertrand (Limnology and Oceanography, 2024)
The recruitment of marine species in isolated oceanic island systems can be challenged by prevailing currents, as exemplified by the Tropical Southwestern Atlantic. In this region, the Fernando de Noronha ridge hosts several seamounts, the Rocas Atoll and the Fernando de Noronha Archipelago, which are home to great marine biodiversity. However, along the ridge, the central branch of the South Equatorial Current (cSEC), flowing westward, poses a challenge to the recruitment of organisms toward Fernando de Noronha. To unveil critical insights into the intricate processes shaping biodiversity in these insular ecosystems, we use a dispersal Lagrangian tool to explore the role of diel vertical migration (DVM) to depth strata influenced by the South Equatorial Undercurrent (SEUC), which flows eastward bellow the cSEC, in shaping species dispersal and metacommunity dynamics. Our results show that while not a direct journey, the DVM into SEUC‐influenced strata increases the possibility that the seamounts and the Rocas Atoll act as stepping stones between the continental shelf and Fernando de Noronha. Propagules of organisms originating primarily from the continental shelf are transported to the western seamounts of the ridge. Upon reaching the western seamounts, organisms can find suitable habitats to recruit. The progeny of these communities that migrate to SEUC‐influenced strata have the opportunity to reach suitable habitats at the Rocas Atoll and the Eastern seamounts, ultimately connecting to the Fernando de Noronha archipelago. These results provide scientific fundaments for the development of a functional network of marine protected areas in the Tropical Southwestern Atlantic.

Role of indigenous microorganisms and organics in the release of iron and trace elements from sediments impacted by iron mine tailings from failed Fundão dam - Alex S. Santos; Bernardo F. Braz; Pedro Sanjad; Ana Caroline R. Cruz; Miriam A.C. Crapez; Reiner Neumann; Ricardo E. Santelli; Carolina N. Keim (Environmental Research, 2023)

Planktonic cnidarian responses to contrasting thermohaline and circulation seasonal scenarios in a tropical western boundary current system - Everton Giachini Tosetto; Arnaud Bertrand; Sigrid Neumann-Leitão; Alex Costa da Silva; Miodeli Nogueira Júnior (Ocean Science, 2022)
In western boundary current systems (WBCSs), strong currents flow coastward carrying oceanic water masses and their associated planktonic fauna. Variation in the intensity of these currents and in the continental runoff may affect the dynamic interplay between oceanic and coastal communities. In addition, changes in the continental runoff and the thermohaline structure modulate the primary production, adding complexity to the dynamics of these oligotrophic systems. These dynamics likely shape the planktonic cnidarian communities. To further understand such relationships, we used a comprehensive dataset encompassing samples collected above the shelf and slope and around oceanic seamounts and islands of the Fernando de Noronha Ridge in the western tropical South Atlantic, in two seasons characterised by distinct thermohaline structure and circulation patterns. Results show that in the tropical South Atlantic and, likely, other western boundary systems with narrow continental shelves, coastward currents spread oceanic waters and their associated cnidarian species over the continental shelf. However, while both coastal and oceanic communities co-occur when the continental runoff is notable, oceanic species dominate almost the entire shelf during the dry season characterised by a stronger boundary current intensity. We also conclude that when the mixed-layer depth and associated nutricline are shallower, the enhanced primary productivity supports larger populations of planktonic cnidarian species through a bottom–up control.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)